Burkitt lymphoma affecting the right heart. A case from practice - R.M. Vitovsky; V.P. Zakharova; O.А. Lozovyy; V.V. Isaenko; O.A. Pishchurin (Кардіохірургія та інтервенційна кардіологія, 2017)
Berkitt lymphoma as a primary malignant tumor of the heart occurs extremely rarely. By the time of the diagnosis, patients already have regional or distant metastases, which greatly worsens their clinical condition and the prognosis of surgical treatment. Hospital mortality in patients with malignant neoplasms is 25–50 %. The article describes an unusual case of Burkitt's lymphoma with heart involvement in a male of 27 years old. Various diagnostic methods were used to determine the nature of the neoplasm. Subsequent treatment methods resulted in a positive long-term outcome.